Waiver of Inheritance, according to law in Kosovo - Vlahna, Kastriote; Kuçi, Hajredin (Journal of World Science, 2023)
The right of inheritance as the main branch of civil law is applicable today as a positive right guaranteed by the constitution, which right any subject of the law can have without differences of gender, ethnicity, or race. The right to inherit dates back to the time of unwritten laws, until today it is defined and protected by state laws. The topic related to the right to legally inherit the parent's inheritance or even the inheritance of someone who is not related by blood to us but made us an heir through the will is debatable and very current. Thus, subjects who are considered heirs must accept or not accept that inheritance after the death of the heir. Precisely for the acceptance or non-acceptance of the inheritance, we come across many cases in practice that end up in a contested procedure, but to clarify the renunciation of the inheritance, this paper has been prepared, which is divided into chapters in which the issue of renunciation is mainly elaborated inheritance, the progress and procedure of how we arrive at a decision which finds that a subject of law who was an heir renounces that inheritance, or does not voluntarily accept the inheritance left by the testator, whether by law or with legal work.